Effect of liming on yield and quality of peppermint and Sachalin mint in fine sand soil of Northern Finland - A. AFLATUNI; J. UUSITALO; S. EK (Scientific Agricultural Society of Finland, 2008)
Soil acidity commonly limits plant production in the fine sand soil of Northern Finland, which often has a low pH (5.5-6.5) and contains low levels of Ca and Mg. The effect of five liming (10% Mg and 19% Ca) levels, 0, 4, 8, 12, and 16 tons ha -1 , on the herb and essential oil yield and menthol and menthone content of two mint species (peppermint, Mentha x piperita, a variety of Black Mitcham and Sachalin mint, Mentha arvensis var. sacchalinensis) cultivated in fine sand soil in Northern Finland (6440N and 2505E) was studied during 1998-2000. Liming clearly increased the pH levels and the Ca and Mg content of the soil. The dry matter content, essential oil quantity, and the menthol or menthone content in mints were not affected by liming. In comparison with no liming however, liming at a rate of 4 t ha -1 doubled the herb yield. The highest yield was achieved in Sachalin mint by liming at 4 or 8 t ha -1 in the second and third year (soil pH 6-6.5) (Ca 725-871 mg l -1 and Mg 122- 219 mg l -1 ), and in peppermint by liming at 4, 8 or 16 t ha -1 (soil pH 6-6.6) (Ca 725-1272 mg l -1 and Mg 122-245 mg l -1 ). Therefore, we conclude that a higher peppermint and Sachalin mint yield is achieved by increasing soil pH to values above 6.0 in the fine sand soil of Northern Finland.;